Fisiologia de Chlorella sorokiniana e Ankistrodesmus densus: efeitos e dinâmica de nanopartículas de cobre - Barreto, Daniela Mariano (Universidade Federal de São Carlos, 2018)
The phytoplankton community is composed of microalgae that support food chains in aquatic ecosystems. In these environments they are immersed in a complex matrix of organic and inorganic substances. In some situations, they are still subject to a range of anthropogenic wastes that end up entering aquatic environments, such as nanoparticles (NPs). Due to the unique characteristics of NPs, their use is intense, even if neither use nor disposal is regularized by competent governamental agencies. Toxicological studies on the effect of NPs on phytoplankton have controversial results. The toxicity of NPs is related to their reactivity, which depends on the size of the particles, formation of aggregates, availability of organic matter, among other factors. In this study, we first sought to understand the dynamics of NPs in algal cultures and followed investigating on the physiological effects of copper NPs (NPs-Cu) on two freshwater Chlorophyta (Chlorella sorokiniana and Ankistrodesmus densus) exposed to nominal NPs-Cu concentrations estimated for the environment (0.57 to 12.70 μg L-1) and above these (up to 635.0 μg L-1). We analyzed parameters related to growth, photosynthesis and intracellular biomolecules under controlled laboratory conditions at 72 h cultures. The results showed that the population growth rate was affected in both microalgae species. The intensity of the photosynthetic processes varied according to the microalgae, with C. sorokiniana being more resistant than A. densus that presented reductions in photosystem II quantum yield, electron transport rates and consequentely in the estimated gross primary productivity. The biochemical composition (proteins, carbohydrates and lipids) was affected in the presence of NPs-Cu in both microalgae, but at environmentally relevant concentrations of NPs-Cu only carbohydrates were affected. Protein synthesis was stimulated at the higher end of the NPs-Cu concentration range, suggesting the production of antioxidant proteins associated with cell detoxification. This study is a contribution to the knowledge of the toxicology of NPs to freshwater microalgae and their possible consequence in natural environment.
Physiology of Chlorella sorokiniana and Ankistrodesmus densus: effects and dynamics of copper nanoparticles
Keywords: Produtividade primária bruta; Carboidratos; Proteínas; Rendimento fotossintético; Taxa de transporte de elétrons; Gross primary productivity; Proteins; Carbohydrates; Photosynthetic yield; Electron transport rate; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::FARMACOLOGIA::TOXICOLOGIA